The Influence of Motivation and Learning Style on Learning Pattern Toward Students’ Speaking Improvement - Khadijah Maming; Ali Wira Rahman; Radiah Azizah Idris (Hasanuddin University, 2023)
In learning, there are three interrelated dimensions to support the learning, namely the cognitive, affective, and psychomotor dimensions. From these learning dimensions, there are learning styles that are included in the cognitive dimension and motivation are included in the affective dimension of learning. This study aims to find out the relationship and influence of motivation and learning style on learning pattern toward speaking improvement of UMPAR English Education students. The researcher applies a qualitative method with a case study approach based on phenomena among students. The respondents in this study consisted of three third-semester students and three fifth-semester students from the English education department UMPAR. In addition, this study conducted semi-structured interviews with students to understand deeper perceptions. The results of the interviews show that there are various student motivations in improving their speaking skills, namely: to train self-confidence, a sense of competition, to develop more, to gain appreciation, presence of a role model, and the support of other people. Apart from motivation, researchers found a learning style that plays a very important role in student learning, namely the auditory learning style with the highest score in all the VARK learning style test results for respondents. The researcher found that there were four classifications of student learning patterns in improving speaking skills, namely: Experience of applying learning media, social interaction, word notice, monologue habits. The results of the research about the influence of motivation and learning styles on learning patterns toward students’ speaking improvement show that there is a positive influence of motivation and learning styles on student learning patterns in improving speaking skills